Hubungan Keamanan Persepsian Terhadap Intensi Muzaki Membayar Zakat Menggunakan Aplikasi Digital - Wininda Qusnul Khotimah; Meita Larasati (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
The purpose of this research is to investigate the relationship of perceived security and the intention of muzaki to use the application of digital transactions in paying zakat. The method of collecting samples in this study used a purposive sampling technique. The sample from this study is muzaki in Indonesia who has paid zakat digitally. This study uses a survey method using a research instrument in the form of a questionnaire. The questionnaire will be distributed to muzaki in Indonesia who have paid zakat digitally via email and google docs. Before testing the hypothesis, the researcher tests descriptive, validity and reliability statistics. All collected questionnaires were analyzed using the Pearson correlation. To measure the dimensions of perceived security, perceived security and intention of muzaki to use the application of digital transactions in paying zakat using a Likert scale, 1 means strongly disagree and 5 means strongly agree. The results of this study prove that perceived security has a positive relationship with the intention of muzaki to use digital applicationsto pay zakat with a significant number of 0.002.